Characterization of patients hospitalized for bronchiolitis according to severity and risk factors. Ghardaia, 2023-2024 - Alexander Torres Molina; Rafael Rosales González (Medisur)
Foundation: more than half of Algerian children under two years of age suffer from bronchiolitis during the epidemic period (November-April), with a peak between January-February; however, evidence in this regard is very rare. Objective: to characterize patients hospitalized for bronchiolitis according to severity and risk factors. Methods: Descriptive study, carried out at the Gueddi Bakir Specialized Hospital Establishment, belonging to the Ghardaia commune, in Algeria, from December 2023-March 2024. In a population of 327 patients admitted for bronchiolitis, the studied variables: age, sex, severity of the disease, risk factors related to the host and environmental factors. Results: Males predominated, with 59.02%. 41.89% were between 6-12 months old and 27.83% were older than one year. According to the Tal scale, 243 cases were stratified as mild, 69 moderate and 15 severe. 60.0% of severe cases were younger than three months, 53.33% suffered from congenital heart disease, had not been breastfed and were regularly exposed to environmental cigarette smoke. Conclusions: Most patients admitted for bronchiolitis had mild symptoms, were male, and were between six months and one year old. The risk factors most frequently observed in severe cases were age under three months, congenital heart disease, not breastfeeding, and exposure to second-hand cigarette smoke.